Análisis de la relación entre el trabajo y el aumento del consumo de alcohol del personal rural que labora en las unidades operativas del ministerio de salud pública, distrito 05d04 Pujilí – Saquisilí, periodo 2015. Propuesta de programa de control. - Arroba Pillajo, Jeanneth Pilar (2015)
Alcohol consumption worldwide is widely distributed, as revealed in data published by the World Health Organization. The Harmful consuption can cause not only physical problems but also in society, family and work. For this reason the aim of this research is to determine that the staff of rural professionals of the District 05D04 Pujilí - Saquisilí the Ministry of Health who fulfill their contract year change of address, situation that increases the consumption of alcohol. A descriptive study was conducted on a sample of 55 rural professionals; of which 41 changed residence. A questionnaire is applied to all of them to obtain data on age, gender, change or not of residence; the AUDIT test is also applied for obtaining data about alcohol intake and classify them by áreas to take decisions regarding the intervention that must be perform. The results obteins show that in the the professionals who changed address to fulfill their contract there was a increase in the consumption of alcohol , but not statistically significant. It is recommended to test all workers in the District to detect alcohol problems and early intervention. . A program of prevention and control based on capacitation, application of AUDIT test and early intervention to all District workers, was designed.